Impact of parental involvement on the communication skills of children with autism - Janine Joy L. Tenerife; Emerson De Luna Peteros; Joseph L. Bunghanoy; Lilibeth C. Pinili; John V. de Vera; Margie D. Fulgencio (Institute of Advanced Engineering and Science, 2023)
In pursuit of every individual’s access to education regardless of one’s statusin life, the Philippines establishedspecial education(SPED) centers to caterto children with special needs.Children with autism are the expectedbeneficiaries of these centers. This research assessed the impact of parentalinvolvement on the communication skills of children with autism at a SPEDcenter in Cebu City, Cebu, Philippines. Their teachers, regardingtheircommunication skills, assessed thirty children with autism. At the sametime, parents were asked to rate their extent of involvement in their child’sschool activities using survey questionnaires. Different statistical tools wereused to treat the data gathered, such as the weighted mean, standarddeviation, andPearsonproduct moment correlation coefficient. Resultsrevealed that parents were involved in the school activities of their children.However, the children had a moderate manifestation of communicationskills. It was found that there is a moderate positive significant relationshipbetween the parents’involvement and the communication skills of thechildren. Thus, teachers are encouraged to design programs for the childrenthat would involvethe parents in enhancing the communication skills ofchildren with autism.